Multi-organ failure caused by lasagnas: A case report of Bacillus cereus food poisoning - Thery, Marin; Cousin, Vladimir L.; Tissieres, Pierre; Enault, Maxime; Morin, Luc (Frontiers in Pediatrics, 2022)
We report a Bacillus cereus, cereulide producing strain, food poisoning of two sisters. After eating a few bites of pasta cooked 3 days earlier, a 13-year-old girl developed mild symptoms. However, her 11-year-old sister suffered, 40 hours after ingestion of the entire platter, a multi-organ failure including acute liver failure, rhabdomyolysis, disseminated intravascular coagulation and acute kidney injury. She received supportive care in pediatric intensive care using mechanical ventilation, hemofiltration, and high-doses vasopressors. She was specifically treated for toxin-mediated disease using blood purification and further digestive decontamination. This report highlights the potential severity of Bacillus cereus food poisoning but also a successful dual treatment including toxin removal and antimicrobial treatment to prevent toxin production.